Changing faecal population of escherichia coli in hospital medical patients. Issue 5683 (6th December 1969) - Cooke, E. Mary; Ewins, Susan; Shooter, R. A.
Abstract : Specimens of faeces were obtained at weekly intervals for one year from patients in a female medical ward and Escherichia coli present were typed. The faecal E. coli population of the patients was constantly changing. No serotypes of E. coli were dominant, but on 31 occasions during the year small clusters of patients carried the same type.